Healthy migrants but unhealthy offspring? A retrospective cohort study among Italians in Switzerland - Tarnutzer Silvan; Bopp Matthias (BMC, 2012)
Abstract Background In many countries, migrants from Italy form a substantial, well-defined group with distinct lifestyle and dietary habits. There is, however, hardly any information about all-cause mortality patterns among Italian migrants and their offspring. In this paper, we compare Italian migrants, their offspring and Swiss nationals. Methods We compared age-specific and age-standardized mortality rates and hazard ratios (adjusted for education, marital status, language region and period) for Swiss and Italian nationals registered in the Swiss National Cohort (SNC), living in the German- or French-speaking part of Switzerland and falling into the age range 40-89 during the observation period 1990-2008. Overall, 3,175,288 native Swiss (48% male) and 224,372 individuals with an Italian migration background (57% male) accumulated 698,779 deaths and 44,836,189 person-years. Individuals with Italian background were categorized by nationality, country of birth and language. Results First-generation Italians had lower mortality risks than native Swiss (reference group), but second-generation Italians demonstrated higher mortality risks. Among first-generation Italians, predominantly Italian-speaking men and women had hazard ratios (HRs) of 0.89 (95% CI: 0.88-0.91) and 0.90 (0.87-0.92), respectively, while men and women having adopted the regional language had HRs of 0.93 (0.88-0.98) and 0.96 (0.88-1.04), respectively. Among second-generation Italians, the respective HRs were 1.16 (1.03-1.31), 1.06 (0.89-1.26), 1.10 (1.05-1.16) and 0.97 (0.89-1.05). The mortality advantage of first-generation Italians decreased with age. Conclusions The mortality risks of first- and second-generation Italians vary substantially. The healthy migrant effect and health disadvantage among second-generation Italians show characteristic age/sex patterns. Future investigation of health behavior and cause-specific mortality is needed to better understand different mortality risks. Such insights will facilitate adequate prevention and health promotion efforts.